Hisbah and Quality Assurance: Learning from Islamic Golden Age Heritage - Tengku Zawaw, Tengku Nurul Sa’adah i; Muhamad, Mohd Dani; Ishak, Amal Hayati (Online Journal of Research in Islamic Studies, 2019)
The current inability of industrial sectors within Islamic countries to produce high-quality products is at stake. Nevertheless, during the Islamic Golden Age, products of the Islamic world were highly demanded and recognized as the best products available. Based on historical records, products’ quality during those times is well-maintained via the functional institution of Hisba. The historical compendiums had narrated on the systematic structure of manuals in quality conformance for various industries of those times. The artisans and merchants were reported to be supervised on the quality of output by enforcers of Hisba, known as Muhtasib, ‘Arif and guilds. With particular emphasis on the institution of Hisba, this article examines the importance of quality from an Islamic perspective. This article also analyzes some aspects of quality assurance that has been practiced during the Islamic golden times. Employing a systematic literature review and content analysis, selected historical compendiums are explored for the abovementioned purposes.